PENDEKATAN SOSIOLOGIS DALAM KAJIAN AGAMA: METODOLOGI STUDI ISLAM - Muhammad Azhar Fauzan; Arya Abdul Alim (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This research discusses the sociological approach in the study of religion, which is an analytical method that views religion as a social phenomenon that lives and develops within society. The method used in this research is library research with a historical-factual and analytical-theoretical approach as well as descriptive-qualitative analysis. The results of this research show that classical sociological figures such as Emile Durkheim, Max Weber, and Karl Marx have laid strong theoretical foundations for the development of the sociology of religion. Durkheim emphasized the function of religion in creating social solidarity and community integration, Weber viewed religion as a motivation for social action and economic change, while Marx criticized religion as part of the ideological structure related to power relations. Furthermore, modern theories such as secularization theory, rationalization, social constructionism, symbolic interactionism, and rational choice theory expand the understanding of religious dynamics in the modern and global era. The conclusion of this research is that the sociological approach provides a comprehensive analytical framework for understanding religion objectively, critically, and contextually, although it has limitations in addressing the spiritual dimension and normative truth. This approach should be used dialogically with other approaches to produce a more complete and balanced understanding.